2021
DOI: 10.1038/s41556-020-00619-0
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Wnt signals regulate cervical squamocolumnar homeostasis and emergence of metaplasia

Abstract: The transition zones of the squamous and columnar epithelia constitute hotspots for the emergence of cancer, often preceded by metaplasia, in which one epithelial type is replaced by another. It remains unclear how the epithelial spatial organization is maintained and how the transition zone niche is remodelled during metaplasia. Here we used single-cell RNA sequencing to characterize epithelial subpopulations and the underlying stromal compartment of endo- and ectocervix, encompassing the transition zone. Mou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 66 publications
5
110
1
Order By: Relevance
“…The organoid cells expressed validated SCJ markers more robustly than classic cell lines and displayed both differentiated endo-and ectocervical cell types. Chumduri et al (2018Chumduri et al ( , 2021) generated endocervical-like, longterm expandable organoids from ecto-and endocervical patient samples, dependent on the presence of Wnt agonists (RSPO1 and WNT3A). They showed differentiation potential toward an ectocervical phenotype by activating the cAMP pathway and hinted toward different originating cells (i.e., squamous cancers from CK7 + and adenocarcinomas from CK7 + CK8 + cells).…”
Section: Cervixmentioning
confidence: 99%
“…The organoid cells expressed validated SCJ markers more robustly than classic cell lines and displayed both differentiated endo-and ectocervical cell types. Chumduri et al (2018Chumduri et al ( , 2021) generated endocervical-like, longterm expandable organoids from ecto-and endocervical patient samples, dependent on the presence of Wnt agonists (RSPO1 and WNT3A). They showed differentiation potential toward an ectocervical phenotype by activating the cAMP pathway and hinted toward different originating cells (i.e., squamous cancers from CK7 + and adenocarcinomas from CK7 + CK8 + cells).…”
Section: Cervixmentioning
confidence: 99%
“…Furthermore, organoids established from human and mouse ecto-and endo-cervical cells revealed that the two epithelial cell types descend from distinct cervical lineage-specific stem cell populations which are regulated by divergent stromal Wnt signals. PDOs from human ecto-and endo-cervical lineages faithfully recapitulated the in vivo architecture and could be maintained in culture for more than six months [12]. Radiation therapy is a mainstay therapy for cervical cancer patients, and the radiosensitivity of cervical cancers is quite diverse.…”
Section: Organoids Recapitulate the Main Characteristics And Tissue Hierarchy Of Epithelial Tumours In Vitro And Are A Potential Tool Formentioning
confidence: 98%
“…The intersection between intrinsic and extrinsic factors in tumour development occurs at the level of the stem-cell compartment, which is regulated by paracrine signalling. A recent study in mice demonstrated that the Wnt gradient defines the border between endocervical columnar epithelium and squamous epithelium of the ectocervix, where likely two different populations of stem cells are regenerating epithelial compartments depending on the signalling received from the stroma [12]. While expression of Krt5/Krt14 markers characterize squamous epithelium, columnar lineage exhibits hallmark expression of Krt8/Krt19.…”
Section: Changes In Stemness During Transformationmentioning
confidence: 99%
“…The mucosal epithelium of different organs often exposed to extrinsic factors like diet, toxins, and microbes are predisposed to carcinogenesis. Epithelial transition zones where two different epithelial types meet represent hotspots of preneoplastic metaplasia, altered microbiota and cancer development [1][2][3][4] . Gastroesophageal junction (GEJ) is one of those transition zones defined by the Z-line where the mucosa of the distal esophagus and the proximal stomach meet.…”
Section: Introductionmentioning
confidence: 99%